1995
DOI: 10.1016/0895-7061(95)00116-7
|View full text |Cite
|
Sign up to set email alerts
|

Essential hypertension predicted by tracking of elevated blood pressure from childhood to adulthood: The Bogalusa heart study*

Abstract: It is well known that blood pressure (BP) levels persist over time. The present investigation examines tracking of elevated BP from childhood to adulthood and its progression to essential hypertension. In a community study of early natural history of arteriosclerosis and essential hypertension, a longitudinal cohort was constructed from two cross-sectional surveys > 15 years apart: 1505 individuals (56% female subjects, 35% black), aged 5 to 14 years at initial study. Persistence of BP was shown by significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
384
2
27

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 647 publications
(422 citation statements)
references
References 36 publications
9
384
2
27
Order By: Relevance
“…2,3,7,9,29 These factors were also found in the final models for the prediction of rising in quartile through this 11-year follow-up. The models in the present study were not designed to predict followup BP but to compare subjects who moved to a higher quartile with subjects who either stayed or declined to a lower quartile.…”
Section: Prediction Of Trackingmentioning
confidence: 74%
See 2 more Smart Citations
“…2,3,7,9,29 These factors were also found in the final models for the prediction of rising in quartile through this 11-year follow-up. The models in the present study were not designed to predict followup BP but to compare subjects who moved to a higher quartile with subjects who either stayed or declined to a lower quartile.…”
Section: Prediction Of Trackingmentioning
confidence: 74%
“…The degree of tracking of BP, weight, height and BMI as well as the almost identical tracking correlations in males and females were in general within the same range found in other longitudinal studies concerning tracking from childhood to adulthood. 2,3,5,19,[21][22][23] The minor discrepancy between the studies could be due to differences in measurement procedures, follow-up losses (dropouts) 24 or length of follow-up period. Studies of BP tracking have shown lower correlation coefficients with increasing length of time between examinations.…”
Section: Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated blood pressure levels in children strongly indicate that they will suffer from hypertension as adults. 4,5 Studies also demonstrate that the prevalence of hypertension among US children increased from 2.1 to 3.0% between 1988 and 2006 (McCrindle 6 ; Ostchega et al 7 ) and 16.1-22.9% between 2004 and 2007 in Greece. 8 Pre-hypertension is a high risk for developing hypertension, which may also lead to coronary heart disease.…”
Section: Introductionmentioning
confidence: 98%
“…13,14 The growing obesity epidemic may contribute to an unexpected increase in the number of children with hypertension. 15,16 Since childhood hypertension is associated with adulthood hypertension and other chronic diseases, 4 previous studies advocate the early detection and prevention of childhood hypertension. 11,15,[17][18][19] In Taiwan, the increasing availability of high fat, high calorie foods has contributed to the continually increasing obesity levels of adults and children.…”
Section: Introductionmentioning
confidence: 99%